MULTI-PRODUCT MASTER PRODUCTION SCHEDULING OPTIMIZATION MODELLING USING MIXED INTEGER LINEAR PROGRAMMING AND GENETIC ALGORITHMS - Al-Ashhab, M. S.; Fadag, Hassan (International Journal of Research -GRANTHAALAYAH, 2018)
The objective of this research is to develop a Master Production Scheduling (MPS) model to maximize the total profit using Mixed Integer Linear Programming (MILP). The model is solved using both MILP with the Xpress software and genetic algorithms with the Evolver solver. The model is built for Evolver in MS Excel. Results of both solving tools are compared to analyze the performance of each of them. The accuracy and capability of the model to solve the MPS problems have been verified through the discussion of its results logicality for different cases of different patterns.